GROWTH OPPORTUNITY DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PERIODE 2018-2021 - Khotimah, Khosnul; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Economic growth is a measure of a country's progress can be measured by the production sector. Food and beverage company growing rapidly at this time, because it is one of the needs of society in general, the more widespread expansion is expected to deliver contribution to society and the company.The purpose of this research is to analyze and test the influenceGrowth Opportunity and Firm size Against Company Value in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange With Profitability as an Intervening Variable for the 2018-2021 period. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique used was purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The iresults iof ithe idirect iinfluence ihypothesis itest iusing ithe iSmart iPLS i3.0 iapplication, ishow ithatGrowth iOpportunity ipositive isignificant ieffect ion iProfitability,Firm isize ipositive ibut inot isignificant ieffect ion iProfitability,Growth iopportunity inegative ibut inot isignificant ieffect ion ifirm ivalue,Firm isize ihas ia isignificant ipositive ieffect ion ifirm ivalue, iProfitability ihas ia isignificant ipositive ieffect ion ifirm ivalue,Growth iopportunity ipositive isignificant ieffect ion ifirm ivalue ithrough iprofitability,Firm isize ihas ia ipositive ibut inot isignificant ieffect ion icompany ivalue ithrough iprofitability.